Background, Origins and Changes of the Lithuanian Business Elite Companies 1995–2004 - Šimkus, Vilius (Lietuvos istorijos studijos, 2024)
The article analyses the largest Lithuanian companies, their background, change, origin and other major characteristics in the period of 1995–2004. This period was chosen because it was only from 1995, after the end of the first phase of privatisation, that a layer of major entrepreneurs emerged in Lithuania, which was undergoing the most significant changes until 2004. The study uses lists of the largest Lithuanian companies by turnover, covering 200 companies for each selected year. The analysis focuses on the factors which contributed most to the change in these lists, and on the way how the companies on the lists changed in terms of the year of their establishment, place of establishment, economic sectors, and financial indicators. A separate part of the paper is devoted to the origin of the largest business enterprises, while identifying and analysing change in terms of the origin. The study makes use of various encyclopaedic and media sources and the statistical data, published memoirs and interviews. The analysis shows that the largest business enterprises in Lithuania changed fundamentally during the period under consideration, especially in terms of the dominant economic sectors and the origin of the business.